"When no-one's looking, " the application of lung recruitment and normal saline instillation with paediatric endotracheal suction: An exploratory study of nursing practice. Issue 1 (January 2019) - Schults, Jessica A.; Cooke, Marie; Long, Debbie; Mitchell, Marion L.
Abstract: Background: The complex nature of the Paediatric Intensive Care Unit (PICU) patient requires the bedside nurse to make rapid, complex decisions regarding endotracheal suction (ETS) interventions. It is not understood what influences nurses' decision making in the context of ETS, however, the actions of the clinician have a direct impact on the efficacy of the ETS event and patient outcomes. Objectives: To explore and describe the use of normal saline instillation and lung recruitment with paediatric ETS in a cohort of Australian nurses, and to identify factors that influence normal saline use with ETS. Methods: A descriptive, exploratory study. An evidence-based practice model formed the conceptual basis for the study. Semi-structured interviews were conducted with 12 nurses from an Australian tertiary referral paediatric intensive care unit. Audiotaped interviews were transcribed. Inductive thematic analysis was used to code and analyse the interview data and identify themes. Findings: Data analysis revealed three themes: patient's clinical presentation, clinician judgement and unit practice norms. Conclusions: Variability in nurses ETS practice was marked. In the absence of evidence based clinical guidelines, nurses relied on knowledge derived from clinical experience and the local setting to guide NSI and LR intervention decisions. Participants reported uncertainty regarding ETS best practice and perceived the lack of research evidence as a barrier to making informed clinical decisions at the bedside. Rigorous research evaluating the safety and efficacy of NSI and LR with ETS is urgently required for patient care; however PICU nurses rely on multiple sources of evidence to inform ETS practice decision.